A comprehensive approach in developing akhlaq: a case study on the implementation of character education at Pondok Pesantren Darunnajah - ., Duna Izfanna; Ismail, Nik Ahmad Hisham (Emerald Group Publishing Limited, 2012)
Purpose- The purpose of this paper is to describe how a unique Islamic education system, named Pondok Pesantren, implemented and contributed substantially to the character education of its student. Design/methodology approach- In total, 12 teachers and 24 students of Pondok Pesantren Darunnajah, Indonesia were interviewed, participated in focus group discussion, and were observed. Findings- Findings suggest that Pondok Pesantren Darunnajah adopts the comprehensive approach of character education which is laid on Islamic values as its ultimate philosophy. The majority of teachers and students reported that the POndok Pesantren Darunnajah educates and develops students' character by infusing knowledge, providing supportive conditions on environment, then giving chances to practice and form. Originality/value- The paper proposes a model character education at Pondok Pesantren, as well as other Islamic education systems which have similar characteristics on the implementation of character education. Recommendations for future researches and practice also presented.